Impressing for Success: A Gendered Analysis of a Key Social Capital Accumulation Strategy - Kumra, Savita; Vinnicombe, Susan (Wiley, 2010)
Social capital theory assesses the career benefits that accrue to individuals from the stock of relationships they have. Such benefits can be in the form of guidance and advice, access to key projects and assignments and help with setting up business deals. However, when assessing whether such career-enhancing resources are available equally to men and women, we find that gender impacts on the access to and accumulation of social capital. The article seeks to address two key research questions. The first is whether women are aware of the need to accumulate social capital to advance their careers and the second is whether they use impression management techniques in order to assist them in doing this. Findings are reported from a study in an international consulting firm with 19 female consultants. In respect of research question one the findings indicate that women in the sample are aware of the need to accumulate social capital to advance their careers; with particular emphasis being placed on the importance of gaining access to influential sponsors. In respect of research question two, the findings confirm that women in the sample do perceive the necessity to utilise impression management techniques to help them to accumulate social capital. This is done in a defensive way and is linked to ensuring that one is seen as ambitious, likable and available. It is argued that these are key organizational norms, and it is perceived that in order to accumulate social capital, women need to actively work to dispel the negative stereotypes that attach to them because of their gender. The article calls for greater recognition of the impact that masculine organizational cultures have on the career development of women, who not only have to perform at a high level but are also required to expend additional energy conforming to masculine organizational cultures they have had little say in creating.